Multi-omic approaches to investigate meat quality variation - Zhai, Chaoyu, author; Nair, Mahesh N., advisor; Prenni, Jessica E., committee member; Chicco, Adam J., committee member; Belk, Keith E., committee member (Colorado State University. Libraries, 2022)
Variation in the proteome profile of longissimus lumborum (LL) and psoas major (PM) post-rigor influences meat quality attributes such as tenderness and color stability during retail display. Tandem mass tag (TMT) labeling is a chemical labeling approach using isobaric mass tags for accurate mass spectrometry-based quantification and identification of biological macromolecules. The objective of first study was to use TMT labeling to examine proteome profile variation between beef LL and PM during the early postmortem period (45 min, 12 h, and 36 h). We identified a total of 629 proteins, of which 71 were differentially abundant (fold change > 1.5, P < .05) from three comparisons between the muscles (PM vs. LL at 45 min, 12 h and 36 h). These proteins were mainly involved in oxidative phosphorylation and ATP-related transport, tricarboxylic acid cycle, NADPH regeneration, fatty acid degradation, muscle contraction, calcium signaling, chaperone activity, oxygen transport, as well as degradation of the extracellular matrix. At early postmortem, more abundant antiapoptotic proteins in LL could cause high metabolic stability, enhanced autophagy, and delayed apoptosis, while overabundant metabolic enzymes and pro-apoptotic proteins in PM could accelerate the generation of reactive oxygen species and initiation of cell death. Pulmonary hypertension is a noninfectious disease of cattle at altitudes > 1524 m (5,000 ft). Mean pulmonary arterial pressures (PAP) are used as an indicator for pulmonary hypertension in cattle. High PAP cattle (≥50 mmHg) entering the feedlot at moderate elevations have lower feed efficiency as compared to low PAP cattle (< 50 mmHg). In second study, the impact of pulmonary arterial pressure on mitochondrial function, oxidative phosphorylation (OXPHOS) protein abundance, and meat color was examined using LL from high (98 ± 13 mmHg; n = 5) and low (41 ± 3 mmHg; n = 6) PAP fattened Angus steers (live weight of 588 ± 38 kg) during early postmortem period (2 and 48 h) and retail display (days 1 to 9), respectively. High PAP muscle had greater (P = 0.013) OXPHOS-linked respiration and proton leak-associated respiration than low PAP muscles at 2 h postmortem but rapidly declined to be similar (P = 0.145) to low PAP muscle by 48 h postmortem. OXPHOS protein expression was higher (P = 0.045) in low PAP than high PAP muscle. During retail display, redness, chroma, hue, ratio of reflectance at 630 and 580 nm, and metmyoglobin reducing activity decreased faster (P < 0.05) in high PAP steaks than low PAP. Lipid oxidation significantly increased (P < 0.05) in high PAP steaks but not (P > 0.05) in low PAP. The results indicated that high PAP caused a lower OXPHOS efficiency and greater fuel oxidation rates under conditions of low ATP demand in premortem beef LL muscle; this could explain the lower feed efficiency in high PAP feedlot cattle compared to low PAP counterparts. Mitochondrial integral function (membrane integrity or/and protein function) declined faster in high PAP than low PAP muscle at early postmortem. LL steaks from high PAP animals had lower color stability than those from the low PAP animals during simulated retail display, which could be partially attributed to the loss of muscle mitochondrial function at early postmortem by ROS damage in high PAP muscle. Rapid Evaporative Ionization Mass Spectrometry (REIMS) is a type of ambient ionization mass spectrometry, which enables real-time evaluation of several complex traits from a single measurement. The objectives of third study were (1) to investigate the capability of REIMS to accurately identify and predict cooked sheep meat flavor and carcass characteristics based on consumer response utilizing metabolomic data acquired from different types of raw sample by I-Knife and (2) to compare the data generated by these two electrodes (Meat Probe vs. I-Knife) in their ability to differentiate carcass background and sheep meat flavor. Current study demonstrated that REIMS analysis of raw meat samples can be used to accurately predict and classify cooked sheep meat flavor and carcass characteristics (based on consumer response). Specifically, the lean and fat tissue collected at 45 min postmortem can be used to predict carcass characteristics and post rigor meat flavor. Models for diet, flavor intensity acceptance, off flavors presence, overall acceptance, age, and flavor acceptance achieved prediction accuracies higher than 80%. In addition, data generated using the Meat Probe resulted in models with better or similar prediction accuracies of carcass background (age, diet, and gender) and consumer preference (intensity acceptance, flavor acceptance, off flavors presence, and overall acceptance) as compared to models based on data generated using the I-Knife. The Meat Probe was more user-friendly, faster, and cleaner than I-Knife for REIMS analysis. Further investigations are necessary to evaluate the use of the Meat Probe for REIMS analysis in other applications.
Zip file contains data CSVs.